Adsorption Kinetics Emulation With Lattice Gas Cellular Automata - Sun, Baichuan (2017)
Lattice gas cellular automata (LGCA), as a fluid dynamic simulation method, are conceptually simple and can be applied to deal with thermal interface effects to a wide array of boundary conditions. Based on LGCA, the lattice Boltzmann method has been successfully used to model a number of typical continuous fluid dynamic problems. In this research, however, we extend the general Frisch, Hasslacher, and Pomeau method from LGCA to the microscopic scale to emulate the surface adsorption process. Specifically, hexagonal grids topology and geometry are applied in two dimensions with 6-bit digits to represent different states of each grid node. The rule space is then determined as 66. A two-dimensional porous network is constructed for simulating a practical adsorbent material structure. The lattice gas collision and movement are implemented within periodic space boundary conditions. Local rules of lattice gas interaction with network surface are defined and examined. The adsorption probabilities on each adsorptive site, corresponding to adsorption potential with relationship to temperature, are taken into account. As a result, an intuitive visualization of physical surface adsorption kinetics is achieved.